Gap Analysis in Employees and Customers Perspective towards Community Development Effectiveness - A Study of Infosys: A Study on the Perception of Infosys' Community Development Endeavors by Employees and Customers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is an established fact that community development is positively correlated with economic development. All the stakeholders to community development endeavours of corporate sector viz the organisation undertaking it, community towards whom these are direct at and the government have started looking it as a game changer. Whereas corporate sector look it as a deal to invent for it the image of a true corporate citizen, the community and government sees it as tool for economic and social development. The success of any community development endeavour is dependent upon how the same is appreciated by community. If the community thinks of it as the company speaks about it the community development endeavour may be treated as successful. The present study has made an attempt to see if community development endeavours of Infosys, India’s largest Information Technology (IT) Corporation are thought of us similar by community as the same are preached by its managers.